Training in Bariatric and Metabolic Endoscopic Therapies - Pichamol Jirapinyo; Christopher C. Thompson (Korean Society of Gastrointestinal Endoscopy, 2018)
Bariatric endoscopy is an emerging subspecialty for gastroenterologists encompassing a broad array of procedures including primary endoscopic bariatric and metabolic therapies and the treatment of complications of bariatric surgery. In addition, comprehensive understanding of lifestyle intervention and pharmacotherapy are essential to successful outcomes. This review summarizes goals and steps of training for this emerging field.